POTENSI UNSUR-UNSUR KEKRIYAAN (CRAFTMANSHIP) DALAM PAMERAN BIENNALE JOGJA VIII 2005 “DI SINI DAN KINI” - Suryo Tri Widodo, S.Sn. (Ars: Jurnal Seni Rupa dan Desain, 2006)
Craftsmanship elements is always can be found in many kind o f visual arts ivork. These elementsmay include in technicals, materials, concepts, forms, and decorative aspects. Up to now, craftsmanshipelements not only in kriya art, but they also exist in another visua. arts fields. New phenomenon anddevelopment in kriya art is always happen and parallel with 'the neto spirit'of each period, without limited.Craftsmanship elements is also appeared in Biennalle Jogja VIII2005 exhibition. In this article, we will tryto see and describe craftsmanship elements on a few sample visual art works, which is shown in BiennaleJogja VIII2005,4-22 December 2005, on theme "Di Sini dan Kini" (Consciousness o f the Here and Now).Key words: Crafttnanshipelement, Contemporer, Biennale Joya